Spatial Analysis of Olive Presses and Their Role in Economic Development in Gharyan City Using GIS - Ibtesam Omar Al-Dhabi (Journal of Scientific and Human Dimensions, 2026)
The olive tree represents a vital natural heritage in Gharyan City and serves as a fundamental resource for supporting the local economy. However, this heritage faces various obstacles, most notably the declining interest among younger generations. Recently, serious efforts have emerged in Gharyan to revitalize this resource and achieve international recognition through participation in global competitions. This study aims to highlight the developmental importance of olive trees and analyze the spatial distribution of olive presses in Gharyan using Geographic Information Systems (GIS). The study followed a descriptive and analytical approach, utilizing field studies and GIS tools to map and evaluate the distribution of presses. The results indicate that Gharyan possesses high-quality olive oil production and significant potential for economic growth, although the distribution of modern presses requires further support to keep pace with production levels. The study recommends encouraging economic research on olive trees, providing agricultural loans to increase the number of modern presses, and enhancing local support for farmers to ensure the sustainability of this natural heritage.